Mangifera indica disease for smart agriculture monitoring (MiDSAM) / Nik Afiqah N. Ahmad Yani ... [et al.] - N. Ahmad Yani, Nik Afiqah; Mohd Fauzi, Shukor Sanim; Mohd Zaki, Nurul Ain; Mohd Shahidan, Nadia Nabilla; Mat Nazir, Eliy Nazira (College of Built Environment, 2023)
Mangifera indica disease for smart agriculture monitoring (MiDSAM) is an advance technology implementing geospatial and machine learning approaches to provide an early disease identification in Mangifera indica crops, utilizing image datasets from unmanned aerial vehicle (UAV).